Association between anterior pelvic tilt, posterior Pelvic tilt and low back pain - J.MUTHUKUMARAN; S.B. VENKATESH (International Journal of Pharma and Bio Sciences, 2017)
To evaluate the association between anterior pelvic tilt, posterior pelvic tilt and physical dysfunction among low back pain patients. OBJECTIVE: To investigate the association between anterior pelvic tilt, and physical dysfunction among back pain patients. To investigate the association between posterior pelvic tilt and physical dysfunction among back pain patients. METHODOLOGY: A total 60 male subjects Aged between 45- 60 years were selected based on the inclusion and exclusion criteria using quota sampling. In this study for all the participants anterior pelvic tilt assessment, posterior pelvic tilt assessment and low back pain disability evaluation by Modified Oswetry Disability Questionnaire (MODQ) were performed. Strengthening exercises was given for the weakened structures and stretching exercise was given for shortened structures, if it is identified from anterior pelvic tilt, posterior pelvic tilt.RESULT: From Data Analysis made with the quantitative data revealed that both groups are statistically significant between Anterior and posterior pelvic tilt. Statistical Analysis of post test for functional disability revealed that there is slight moderate disability between groups. CONCLUSION: Results of the study shows that there is a significant difference exists in bothanterior and posterior pelvic tilt exercise regimes more patients having anterior pelvic tilt than posterior pelvic tilt.